Fisher vectors for PolSAR image classification - Redolfi, Javier Andrés; Sánchez, Jorge Adrián; Flesia, Ana Georgina (2024)
Artículo finalmente publicado en: Redolfi, J. A., Sánchez, J. A. y Flesia, A. G. (2017). Fisher Vectors for PolSAR Image Classification. IEEE Geoscience and Remote Sensing Letters, 14 (11), 2057-2061. https://doi.org/10.1109/LGRS.2017.2750800